2018
DOI: 10.1507/endocrj.ej17-0384
|View full text |Cite
|
Sign up to set email alerts
|

Transducin β-like 1, X-linked and nuclear receptor co-repressor cooperatively augment the ligand-independent stimulation of TRH and TSHβ gene promoters by thyroid hormone receptors

Abstract: Mutations in TBL1X, a component of the nuclear receptor co-repressor (N-CoR) and silencing mediator of retinoic acid and thyroid hormone receptor co-repressor complexes, have recently been implicated in isolated central hypothyroidism (CeH). However, the mechanisms by which TBL1X mutations affect negative feedback regulation in the hypothalamus-pituitary-thyroid axis remain unclear. N-CoR was previously reported to paradoxically enhance the ligand-independent stimulation of TRH and TSHβ gene promoters by thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Recently, Takamizawa et al . (49) have demonstrated that the ligand-independent thyroid hormone receptor-mediated stimulation of TSHB and TRH promoters was enhanced by TBL1X alone or by cotransfection with TBL1X and NCoR (Fig. 2c); however, the stimulating effect was attenuated by cotransfection with TBL1X mutants (p.Asn365Tyr and p.Tyr458Cys) and NCoR (Fig.…”
Section: Tbl1x Deficiencymentioning
confidence: 90%
“…Recently, Takamizawa et al . (49) have demonstrated that the ligand-independent thyroid hormone receptor-mediated stimulation of TSHB and TRH promoters was enhanced by TBL1X alone or by cotransfection with TBL1X and NCoR (Fig. 2c); however, the stimulating effect was attenuated by cotransfection with TBL1X mutants (p.Asn365Tyr and p.Tyr458Cys) and NCoR (Fig.…”
Section: Tbl1x Deficiencymentioning
confidence: 90%
“…The co-transfection of two TBL1X mutants identified in CeH patients (N365Y and Y458C) with NCoR1 showed impaired co-activation of the ligandindependent activation of the TRH promoter by TR. Of note, N365Y exerted significantly more potent inhibitory effects than Y458C on the ligand-independent stimulation of TRH and TSHβ gene promoters enhanced by NCoR1 (Takamizawa et al 2018). Impaired hearing in patients with TBL1X mutations is unexplained at this moment.…”
Section: Congenital Central Hypothyroidismmentioning
confidence: 92%
“…However, the molecular mechanisms by which mutant TBL1X proteins functionally disturb the negative feedback regulation of hypothalamic TRH and/ or pituitary TSHβ gene transcription by TH have not yet been elucidated. Takamizawa et al (Takamizawa et al 2018) reported that knockdown of endogenous TBL1X in N-1 cells (a hypothalamic neuronal cell line) using siRNA significantly attenuated the NCoR1-mediated enhancement of promoter activity in the presence of unliganded TR. The co-transfection of two TBL1X mutants identified in CeH patients (N365Y and Y458C) with NCoR1 showed impaired co-activation of the ligandindependent activation of the TRH promoter by TR.…”
Section: Congenital Central Hypothyroidismmentioning
confidence: 99%
“…However, genes involved in the negative feedback regulation of the HPT-axis like TSHB and TRH are negatively regulated by T3 which means that their transcription is increased in the absence of T3. It was shown that the c.1145_1147del p.(Asn382del), c.1246A>T p.(Asn416Tyr) and c.1526A>G p.(Tyr509Cys) (NM_005647.3) variants resulted in reduced stimulation of TSHB and TRH promoters in a hypothalamic cell line ( 45 , 46 ). Consequently, this may alter HPT-axis functioning to the point that the hypothalamus and pituitary are resistant to low TH levels, with a possible negative shift of the FT4 set-point.…”
Section: Etiologymentioning
confidence: 99%